The investigative trends on peri-urban area viewed geographic perspective and issue: A bibliometric study - Singkawijaya Elgar Balasa; Nandi Nandi (E3S Web of Conferences)
The peri-urban area represents a transitional zone between rural and urban landscapes, characterized by a mix of village-like and city-like features in physical form, social activities, and development patterns. This article provides an overview of peri-urban landscapes from a geographic perspective, based on a bibliometric analysis of research published from 2000 to 2023. Using data from the Scopus database, the study analyzed 118 publications with 3,464 citations, identifying 2014 as the peak year with 14 publications. The United States emerged as the most influential country, contributing 26 publications and maintaining 20 international collaborations. The research highlights that peri-urban areas are dynamic spaces influenced by geographic perspectives on study areas, models, scales, landscapes, development, and transformation processes. These areas are marked by social, economic, environmental, and spatial diversity. The study emphasizes the importance of geospatial technologies in exploring sustainable development strategies and calls for an interdisciplinary approach to address global challenges such as economic growth, land use changes, and urban planning in peri-urban regions.